2009
DOI: 10.1016/j.tsf.2009.02.069
|View full text |Cite
|
Sign up to set email alerts
|

Structural and electrical properties of Al doped ZnO thin films deposited at room temperature on poly(vinilidene fluoride) substrates

Abstract: Transparent, conducting, Al-doped ZnO films have been deposited, by dc and pulsed dc magnetron sputtering, on glass and electroactive polymer (poly (vinylidene fluoride)-PVDF) substrates. Samples have been prepared at room temperature varying the argon sputtering pressure, after optimizing other processing conditions. All ZnO:Al films are polycrystalline and preferentially oriented along the [002] axis. Electrical resistivity around 3.3x10-3 Ω.cm and optical transmittance of ~85% at 550 nm have been obtained f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…4d, is around 73.2 eV whose value lies between that of Al 2 O 3 film (74.8 eV) and metallic aluminum (72.7 eV). Consequently, it could be predicted that Al atoms substitute for Zn atoms in AZO films which could act as Al donors [20]. Minami et al [12] showed that, in the resultant AZO films deposited by RF magnetron sputtering with sintered ceramic target, the aluminum was always introduced in the form of Al 3+ and that the dopant content in the film was irrelevant to T s below 400 • C, which is just the case in our study.…”
Section: Structural Propertiesmentioning
confidence: 45%
See 2 more Smart Citations
“…4d, is around 73.2 eV whose value lies between that of Al 2 O 3 film (74.8 eV) and metallic aluminum (72.7 eV). Consequently, it could be predicted that Al atoms substitute for Zn atoms in AZO films which could act as Al donors [20]. Minami et al [12] showed that, in the resultant AZO films deposited by RF magnetron sputtering with sintered ceramic target, the aluminum was always introduced in the form of Al 3+ and that the dopant content in the film was irrelevant to T s below 400 • C, which is just the case in our study.…”
Section: Structural Propertiesmentioning
confidence: 45%
“…In contrast, the asymmetric Auger signals, Zn L 3 M 45 M 45 in Fig. 4c comprise a higher energy peak (∼497 eV) which are ascribed to the bonding of Zn with oxygen in the ZnO lattice and, in contrast, a shoulder peak (∼494 eV) which corresponds to the existence of Zn interstitials in the films that are one of the major sources of free electrons in doped ZnO films [15,19,20]. Similarly, there is no T s dependence on the intensity of Auger signals.…”
Section: Structural Propertiesmentioning
confidence: 93%
See 1 more Smart Citation
“…In the case of coatings deposited on PVDF, the minimum value for the film resistivity was 1.7x10 -3 Ω⋅cm. The roughness of the PVDF substrate leads to a higher resistivity when compared to the values obtained for films deposited on glass [24].…”
Section: Electrical Propertiesmentioning
confidence: 63%
“…Representative TCO films are indium tin oxide (ITO), zinc oxide (ZnO) and aluminum zinc oxide (AZO) [3][4][5]. Among the TCO films investigated, ITO is the most widely used material owing to its good conductivity, low electrical resistivity, wide band gap (~3.5 eV) and high transmission in the visible range and near-IR regions of the spectrum [1,2].…”
Section: Introductionmentioning
confidence: 99%